AB0199 Ultrasound Examination in Ra Patients Achieving Comprehensive Disease Control (CDC) or Clinical Remission after 1 Year Follow-Up and T2t Strategy: Real Life Experience from A Single Center, Early Arthritis Clinic. (15th July 2016) - Farina, I.; Galuppi, E.; Sergi, S.; Bergossi, F.; De Giorgio, C.; Ciancio, G.; Govoni, M.
Abstract : Background: According to international task force recommendations, primary goal of rheumatoid arthritis (RA) treatment is to achieve control of symptoms, prevent structural damage and normalize functional status.Simultaneous achievement of DAS28 PCR remission <2.6, HAQ DI <0.5 and change from baseline in modified Total Sharp Score (SHS)<0.5, has recently defined as comprehensive disease control (CDC). Residual sub-clinical synovitis on ultrasonography/power doppler (US-PD) examination is one of the major driver of radiographic progression, but US-PD evaluation has not been yet included in definition of CDC. Objectives: To analyze the achievement of CDC in an Early Rheumatoid Arthritis (ERA) Cohort after 1 year from diagnosis and to evaluate if this status was also associated to absence of US subclinical active synovitis. Compared US status in patients who achieved CDC with those achieving DAS 28 PCR-REM but not CDC. Methods: ERA patients fulfilling 2010 ACR/EULAR who consecutively attended our Early Arthritis Clinic between 2009–2014 were retrospectively analyzed. Patients with available follow-up of 1 year were included. Standardized therapeutic approach has been performed according to EULAR T2T guidelines. Disease activity and functional disability has been evaluated using DAS28 PCR and HAQ DI every 3 months and after 12 months (T12) from diagnosis. Being more easily applicable in daily practice activity, radiographic progression has been assessed using Simple Erosion Narrowing Score (SENS). Therefore we considered as radiographic non progressors those patients who showed no change in SENS score at 12 months, from baseline (assimilated to <0.5 point change in mHSS). Patients were stratified in CDC-achievers and CDC non-achievers. Among those patients who reached DAS28-REM alone were identified. All patients were evaluated by US-PD of both wrists and II and III metacarpophalangeal. US-PD assessment was drawn at T12, considering as active subclinical synovitis a PD signal ≥1 in more than 1 Joint. Results: 125 patients out of 323 met the inclusion criteria. After 12 month from diagnosis, 30% were CDC-achievers (n=38) and 70% CDC non-achievers (n=87); of this last group, 38, 4% (n=48) achieved REM. 81, 2% (39/48) of patients in REM didn't achieved CDC because of radiographic progression. When comparing US-PD findings in both CDC-achievers and REM 6/38 (15.7%) and 12/48 (25%) respectively showed residual US-PD synovitis. In REM 10/12 (83%) of those with residual synovitis didn't achieve CDC because of radiographic progression. Conclusions: In our Cohort a significant proportion of patients achieved CDC one year after diagnosis and a T2T therapeutic strategy. As already known our findings confirm that clinical remission is not fully protective against radiographic progression in ERA since 83% of those with residual US-PD synovitis did radiographically progress.However, the meaning of residual synovitis observed also in our CDC-achievers patients, although to a lesser amount (15.7%), is still unknown and has to be ascertained in a properly designed prospective study with longer follow-up. References: Emery P et al. Ann Rheum Dis 2014;0:1–10. Disclosure of Interest: None declared